A Survey Of Effective Factors in improvement Of Staff performance based on ACHIEVE Model in the view of managers (senior, administrative and nursing) in teaching hospitals in Isfahan - M Yaghoubi; S karimi; A Hasanzadeh; M Javadi; HA Mandegar; F Abedi (Tehran University of Medical Sciences, 2010)
Background: If a managers try for further income or productivity so they must attentive their staff incentive. One of the most issue in the management process is that managers can distinguish strength of staff but they can't determine their weakness . ACHIEVE model present seven factors ( ability, clarify, help, incentive , evaluation, validity , environment ) that effective to staff performance . and this model help manager to determine cause of performance problem. And create change strategy for solving those problem .Material & Methods: It is descriptive , survey and inferential study , the population is university hospital managers in Esfahan university. data is gathered through achieve questionnaire that supported by member of management faculty.The reliability is supported based on α koren bakh . for analysis of data use spss soft ware .Results: Finding show that : Average number of ability factor is (87/5+12/2) , clarify factor (82/3+14/8), help factor (82/6+15/7) , incentive factor ( 81/4+ 15/4), evaluation factor (77/2+15/6) , validity factor (82/7+ 17/3),and environment factor is (85/2+12/8). and base on Pierson test (p<0/05) all of the factor are effective on staff performance.Conclusion: Today the important problem in health care organization is staff effectiveness . in fact , performance improvement is the most step for organization improvement.